Editorial: is there a role for monitoring intermediate anti‐TNF drug concentrations in IBD? Authors' reply. Issue 8 (31st March 2022) - Roblin, Xavier; Paul, Stephane
LINKED CONTENT: This article is linked to Roblin et al papers. To view these articles, visit https://doi.org/10.1111/apt.16852 and https://doi.org/10.1111/apt.16889